PENGARUH PAJAK PENGHASILAN TERHADAP KESEJAHTERAAN: SUATU MODEL TEORITIS - Suratman, Eddy (Universitas Muhammdaiyah Surakarta, 2009)
Tax affects distortion on economy. To minimize the distortion, the government canonically switches the income resources to income tax from other types of tax deemed to have the least distortion. Furthermore, the increase of this income tax will affect the prosperity of the tax payers. This writing is aimed to develop a theoretical model of: firstly, change effect of income tax on income and leisure; secondly, change effect of income tax on consumptions of private goods and public goods; and thirdly, change effect of income tax on prosperities of tax payers and free rider. This writing indicates that (1) work and leisure hours are bound with time endowment, payment and property income after tax and utility parameter; (2) Income tax increase will promote leisure, thus income after tax will decrease; (3) As individuals, income tax payers can see this change positive or negative; and (4) Free riders will get their prosperity improved from income tax increase.